PENGENALAN BENTUK GEOMETRI DASAR PADA ANAK USIA 5-6 TAHUN MELALUI BUSANA SIAP PAKAI: EDUCATION OF BASIC GEOMETRIC SHAPES IN CHILDREN AGED 5-6 YEARS THROUGH READY TO USE CLOTHES - Salsabila Zahra Alfarist; Tyar Ratuannisa (Universitas Trisakti, 2024)
Learning for children aged 5-6 years requires concrete media so that learning can be conveyed well and students can understand learning easily. One of the problems in learning geometric mathematics is the lack of supporting media. This research aims to create design innovation by applying printing and knitting techniques as visual and sensory media in ready-to-wear clothing products for children aged 5-6 years. This research was conducted using the three-stage design process creation theory method. The research results show the potential for basic geometric shapes to be applied and utilized in ready-to-wear children's fashion products. The application of print and knitting techniques can be designed to give clothing a new style or appearance. Clothing designs using new motifs based on trial results can be a new alternative choice and be involved in the progress of sustainable children's fashion, which is followed by current popular trends.